Mechanisms of Secondary Neuronal Damage in Severe Brain Injury (Part 1) - N. B. Karmen; V. V. Moroz; E. I. Mayevsky (Общая реаниматология, 2011)
Objective: to improve the results of treatment in victims with acute heart failure complicating severe concomitant injury, by optimizing inotropic support and to evaluate the efficiency and safety of combined use of drugs with a different mechanism of positive inotropic action. Subjects and methods. In a prospective randomized clinical trial, 26 victims with polytrauma and coronary heart disease-compromized myocardial contractility received inotropic support as a combination of dobuta-mine and levosimendan (Group 1; n=12) or that of dobutamine and epinephrine (Group 2; n=14). Invasive hemodynamic monitoring (Swan-Ganz) was made every 6 hours for 72 hours. The levels of lactate, troponin I, and brain natriuretic peptide (BNP) were measured. Holter ECG monitoring was also made. The end points of the study were cardiac index (CI), duration of inotropic therapy, length of stay in an intensive care unit (ICU), and development of complications. The differences in the indicators were considered statistically significant atpResults. By the use of combination inotropic therapy, hemodynamic instability was thought to be predominantly manifestations of acute heart failure (ejection fraction, 41±7%; CI, 2.1±0.15 l/min/m2; BNP, 1130±280 ng/dl) in compensated normovolemia (central venous pressure, 12±2 Hg mm; pulmonary artery wedge pressure, 14±1 Hg mm). Mean CI was 3.5±0.14 l/min/m2 in Group 1 patients receiving therapy and 2.6±0.33 l/min/m2 in Group 2 (95% confidence interval (CI), 0.49—0.91;p=0.03). The mean duration of inotropic therapy was 71±10.5 and 102±13.5 hours in Groups 1 and 2, respectively (95% CI, 99—161; p=0.001). In Group 2, cardiac arrhythmias (defined as Lown-Wolf class 3-5), an elevation of serum lactate levels (mean, 3.8±0.8 mmol/l; p<0.05), and a clinically significant increase in troponin-I concentrations (mean, 0.85±0.17 ng/ml; p<0.05) were more frequently recorded than those in Group 1. The victims showed no statistically significant differences in the length of ICU stay. Conclusion. The investigation has yielded clinically significant results suggesting that a combination of dobutamine and levosimendan makes it possible to effectively control hemodynamics in victims with polytrauma and diminished myocardial systolic function and to reduce the duration of inotropic support and the negative effects of catecholamines. Key words: combination inotropic therapy, adrenomimetics, levosimendan, polytrauma, heart failure.